The Effect Of Listening Qur’an Recitation Therapy Towards Physiologic Outcomes Among Neonates Underwent In Neonatal Intensive Care Unit: Meta-Analysis - Wardani, Sholichah Kusuma; Hidayat, Ahmad; Dewi, Desi Dwi Siwi Atika; Suciati, Wahida Yuyun; Masdar, Mahmasoni (Journal of Islamic Nursing, 2026)
Audio stimulation, including Qur'an recitation therapy is broadly utilized within the neonatal intensive care unit (NICU). This study aimed to evaluate the effect of Qur’an recitation therapy compared with routine care on physiological outcomes among neonates admitted to the NICU. A comprehensive systematic review was conducted in PubMed, ScienceDirect, Cochrane Library, Scopus, ProQuest, and ClinicalKey, and the final search was performed on 16 October 2025 in Google Scholar to identify relevant English and Arabic studies comparing Qur’an recitation therapy with routine care. A systematic review was conducted following Preferred Reporting Items for Systematic Reviews and Meta-analyses 2020 (PRISMA) guidelines, with search terms containing "neonate", "Qur'an recitation", "physiological response" and "NICU". A total of 738 neonates, consisting of three quasi-experimental and nine RCTs studies. The RCT trials were subjected to a meta-analysis. The results revealed a substantial difference between the two groups when it came to using Qur'an recitation therapy to reduce heart rate with a standard mean difference (SMD) effect value of -0.437 (p < 0.001), respiratory rate (SMD = -0.463; p < 0.001) and increasing oxygen saturation (SMD = 0.490; p < 0.001).  Our study suggested adopting Qur'an recitation therapy in the regularly care of NICU patients to control their physiology. The timing, duration, type of surah, and schedule of Qur'an recitation therapy can be designed to a neonate's clinical conditions. Future research should concentrate on data collecting that is consistent and well-defined, as well as the use of established terminology for Qur'an recitation therapy. Keywords: Qur’an recitation therapy; neonate; NICU; physiologic outcomes; meta-analysis.